"You Get a PhD and We Get a Few Hundred Bucks": Mutual Benefits in Participatory Action Research?. (August 2020) - Felner, Jennifer K.
Participatory action research (PAR), community-based participatory research, and other participatory approaches continue to gain popularity within the field of public health and allied disciplines in an effort to democratize the production of knowledge and contribute to sustainable community health improvements. Consequently, more students and early-career scholars will elect to incorporate participatory approaches in their dissertations and other early-career research studies in an effort to meaningfully influence community health equity in a variety of contexts. While there is a growing body of literature on the processes and challenges involved in PAR, community-based participatory research, and other participatory research, early-career scholars infrequently critically reflect on and detail learnings from their participatory research studies in the academic literature. I respond to this gap by sharing and reflecting on three critical learning points from my own youth-led PAR dissertation study examining how youth of color experience aging out of LGBTQ (lesbian, gay, bisexual, transgender, and queer or questioning)–supportive youth services. In particular, I interrogate how the processes in our academic–youth partner collaboration shaped the possibility of a mutually beneficial praxis and offer recommendations to other early-career scholars embarking on their own participatory research studies.